Experimental Analysis of the Effect of Printing Parameters of 3D Printer FDM Machine on Dimensional Error and Surface Hardness of PLA+ Material - Ibnu Abdul Rosid; Rama Sahtyawan; Grita Supriyanto Dewi; Putri Noviana Nih Pratama (Jurnal INTECH Teknik Industri Universitas Serang Raya, 2025)
PLA material is one of the most commonly used materials in Fused Deposition Modelling 3D printers for various purposes. The quality of the printed part can be assessed from its dimensional accuracy and surface hardness. The method used to determine the appropriate parameters for achieving optimal results is the 2k factorial design method. The parameters studied include BTT, WT, and FP. The levels for BTT were set at 1 mm and 3 mm, WT were 1 mm and 2 mm, and FP consists of concentric and lines. Statistical analysis revealed that several parameters significantly influence the response. The statistical analysis results show factors with a P-value < 0.05 (α = 0.05). The WDE response shows an interaction between BTT, WT, and FP. The HDE response indicates that the interactions between BTT and WT, BTT and FP, WT and FP, and WT affect HDE. In the SH response, the factors BTT, WT, and the interaction between WT and PT affected SH. Meanwhile, in the LDE response, all factors had P-values > 0.05. This study also found that WT individually affects HDE, WDE, and SH. On the other hand, the WT factor interacts with BTT and FP to affect SH.